2020
DOI: 10.2147/idr.s226215
|View full text |Cite
|
Sign up to set email alerts
|

<p>Virulence and Resistance Determinants of Uropathogenic <em>Escherichia coli</em> Strains Isolated from Pregnant and Non-Pregnant Women from Two States in Mexico</p>

Abstract: Background/Purpose: Uropathogenic E. coli (UPEC) is the main cause of urinary tract infection (UTI) and it is known that pregnant women have a higher risk for UTI. UPEC has a variety of virulence and antibiotic resistance factors that facilitate its pathogenic success and it is crucial to know which are the susceptibility patterns, Extended-Spectrum-β-Lactamase (ESBL) production, virulence genes, pathogenicity islands (PAI), phylogenetic groups and serotypes among strains isolated from pregnant and non-pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
5
26
5
1
Order By: Relevance
“…In this study we found that the clinical isolates obtained were predominantly multidrug resistant (93%) and showed a high resistance to antibiotics implemented in the basic treatment of UTI, mainly aminoglycosides, β-lactams, and cotrimoxazole. These results are in agreement with those reported in previous studies [14,16] in Mexico, which highlights the urgent need to search for therapeutic alternatives for the treatment of UTI.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study we found that the clinical isolates obtained were predominantly multidrug resistant (93%) and showed a high resistance to antibiotics implemented in the basic treatment of UTI, mainly aminoglycosides, β-lactams, and cotrimoxazole. These results are in agreement with those reported in previous studies [14,16] in Mexico, which highlights the urgent need to search for therapeutic alternatives for the treatment of UTI.…”
Section: Discussionsupporting
confidence: 92%
“…In Mexico, there are several reports demonstrating the high resistance of clinical isolates of UPEC to this antimicrobial agent which has led to considering its therapeutic efficacy. However, it would be important to continue with research focused on the determination of local susceptibility profiles for the antibiotics included in the basic treatment for UTI in Mexico, since it is known that resistance profiles can differ depending on the geographic area [14,16,[41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resultados similares fueron reportados por Forson et al (2018) quienes reportaron resistencia a ampicilina (79.3 %), tetraciclina (70.7 %) y trimetoprim/sulfametoxazol (49 %). En estudios previos realizados en México, se observan prevalencias de 100% de resistencia a ampicilina (Ordaz-López et al, 2016;Ballesteros-Monrreal et al, 2020). Diversos reportes en microorganimos Gramnegativos aislados de UTI han demostrado la presencia de β-lactamasas, lo cual se asocia a la alta resistencia a antibióticos β-lactámicos y, particularmente, a ampicilina, carbenicilina y cefalotina, similar a lo reportado en el presente estudio (Ramos et al, 2012;Ifeanyichukwu et al, 2017;Khoshnood et al, 2017;Forson et al, 2018).…”
Section: Resultados Y Discusiónunclassified